Fodor's 2009 Spain - Trefler, Caroline; Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to Spain that features information on accommodations and restaurants for various budgets, and also covers tourist attractions, entertainment, shopping, and more; and includes a foldout map.
Cover title: Spain 2009.
Includes index.
Maps on inside covers.
Young Adult
Keywords: Spain -- Guidebooks; Spain -- Description and travel; Spain -- Guidebooks; Spain -- Description and travel